The Role Of Innovative Technological Developments In Laboratory Medicine (The Review of Diabetic Studies, 2025)
Background: The medical field is developing on the technological grounds by leaps and bounds and Saudi Arabia is no exception to the same. As far as role of innovative technology in the medical laboratories is concerned, most of the urban and semi urban areas of the country have adopted the same and but still there is some lacuna in the rural areas. Then on the other hand the training and development of the respective staff for awareness and adoption of new technology is still in the stage of infancy. This present study will evaluate the scenario in the light of data collected from selected medical laboratories in Dammam and Al Khobar; the two cities of Saudi Arabia. Study Objectives: This study's primary goal is to determine the types and prevalence of cutting-edge technologies utilized in laboratory medicine in Saudi Arabia. It also aims to determine how laboratory workers perceive the advantages and difficulties of these technologies.Materials and Methods: Study is based in the urban areas of Dammam city and semi urban areas of Al Khobar. Some of the rural areas surrounding both the cities will also be included. A sample of 350 technicians, Biomedical engineers, clinical pathologists and LIS specialists was taken from the above said places. Study includes Cross sectional study design and uses Binary Logistic Regression and Chi Square test as statistical tool. SPSS ver. 27.0 will be used to analyze the data.